Comparisons of the ski turn techniques of experienced and intermediate skiers - Müller, E.; Bartlett, R.; Raschner, C.; Schwameder, H.; Benko-Bernwick, U.; Lindinger, St. (Journal of Sports Sciences, 1998)
We compared selected kinematic variables for four different ski turn techniques performed by five experienced and five intermediate male skiers. The four ski turn techniques were the upstem turn, the downstem turn, the parallel turn and the parallel step turn. Each turn was divided into the initiation phase and the first and second steering phases. Most of the statistically significant differences ( P < 0.05) between the two groups were found for the initiation phases of the four turns. Both the hip axis–hand axis angle and the edging angle of the uphill ski were significantly different between the two groups for the upstem turn at the beginning of the initiation phase. For the downstem turn, significant differences between the groups were found at the start of the initiation phase for the hip axis–hand axis angle, the shoulder axis–fall line angle, and the edging angle of the uphill ski. The standard deviation of the distance between the tips of the two skis over the second steering phase also differed significantly between the two groups. For the parallel step turn, significant differences were found at the start of the initiation phase for the edging angle of the downhill ski and the downhill ski to movement direction angle. Significant differences were also found for the edging angle of the downhill ski in the middle of the second steering phase and the shoulder axis to movement direction angle at the end of this phase. For the initiation phase of the parallel turn, significant differences were found for the timing of setting the ski pole, the uphill knee angle at the start of this phase and the range of the knee angle of the uphill leg from the start to the end of this phase. For this turn, significant differences between the two groups were also found for the edging angle of the downhill ski in the middle of the second steering phase and the shoulder axis to movement direction angle at the end of this phase. One of the reasons it was possible to identify a few significant differences only for the turns analysed, was the variability within the intermediate group: for most of the variables analysed, the standard deviation was much higher for the intermediate than for the experienced group.